Organisational management of the time-dependent network for the treatment of acute coronary syndrome - Capitani, Elena; Nante, Nicola; Montomoli, Emanuele; Limbruno, Ugo; Biancofore, Antonio; Aiola, Elio; Mohammed, Ahmed; Taddeini, Federico; Limaj, Sandro; D'Amato, Maria Giovanna; Turillazzi, Roberto; De Luca, Assunta; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Cardiovascular diseases are the leading cause of death in Italy, being responsible for 227,350 deaths in 2020, according to the National Institute of Statistics. The implementation of timely reperfusion therapy is crucial to improve patient outcomes, and time-dependent networks for the treatment of Acute Coronary Syndrome, particularly ST-elevation myocardial infarction, have been established. In Tuscany, the network for the treatment of Acute Coronary Syndrome-ST-elevation myocardial infarction covers a vast area encompassing three Local Health Authorities, including all of South-Eastern Tuscany. Key features include equity of access, patient safety, improving the quality of care, standardization, the enhancement of professional skills, technological innovation, increasing case volumes and multi-professional integration across emergency services, hospital facilities and primary care networks. The Tuscan Acute Coronary Syndrome network provides comprehensive treatment for Acute Coronary Syndrome-ST-elevation myocardial infarction in 12 hospitals with 24-hour hemodynamics laboratories and has been extended to new territories, namely Piombino and the Island of Elba. The aim of the present study was to assess the impact of an analytical system for monitoring times to reperfusion treatment and subsequent actions, in order to improve the performance of the network. Materials and Methods. In this retrospective study, we conducted an analytical evaluation of the network’s performance, including reperfusion treatment times and factors causing delay. The study utilized data on patient transport, times from symptom onset to medical contact, and outcomes from the National Outcomes Program (NOP; “Programma Nazionale Esiti” in Italian). Analytical evaluations in 2021 measured the network’s overall performance and identified the main causes of delay. The treatment process was divided into periods, from symptom onset to coronary reperfusion; interventions such as public awareness campaigns, electrocardiogram tele-transmission, and fast-track transfers were implemented in order to minimize delays. Results. The lowest 30-day mortality rate in Acute Coronary Syndrome patients was recorded in hospitals that treated over 300